Hungarian Monitoring, 24 June 1988 . [Magyar rádiófigyelő], 1988. június 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Comecon-EEC cooperation - Vranitzky interview in Rude Pravo - RFE-Warsaw radio bridge under way - Romanian-American relations Domestic Affairs: - Károly Grósz visits American ambassador - Hungarian Socialist Workers' Party (MSZMP) Central Committee session announcement: personnel and operational changes - New trade union law in preparation - American Hungarians petition to save Transylvanian villages - Tens of thousands of Hungarians attend John Paul II mass in Austria - Transylvanian refugees Külpolitika: - KGST-EGK együttműködés - Vranitzky interjú a Rude Pravo-ban - SZER-Varsó rádióhíd készül - Román-amerikai kapcsolatok Belpolitika: - Grósz Károly fogadta az amerikai nagykövetet - MSZMP KB ülés közleménye: személyi és működési változások - Készülőben az új szakszervezeti törvény - Amerikai magyarok petíciója az erdélyi falvak megmentéséért - Magyarok tízezrei II. János Pál ausztriai szentmiséjén - Erdélyi menekültek ügye